The Influence Of Perceived Diversity Management On Women’s Retention In The IT Industry - C Rani, A.V Lakshmi Brinda, Naiymunnisa Begum (Journal of Informatics Education and Research, 2025)
The retention of skilled professionals, particularly women, is a critical challenge in the Information Technology (IT) industry. Employee turnover results in the loss of talent, institutional knowledge, and business opportunities. Despite this, few studies have specifically examined the factors influencing the retention of female employees in this sector. This research addresses that gap by investigating how perceived diversity management impacts the retention of women in the Indian IT industry. It further explores perceived social support as a moderating factor in this relationship. Grounded in Attitudinal Commitment Theory, the study utilized a cross-sectional research design to collect data from female IT professionals in India through an online questionnaire. A purposive sampling technique was employed to target the appropriate demographic. The data was then analyzed using IBM SPSS, AMOS, and Process macro to test the hypothesized conceptual model, which included mediation and moderation effects. The analysis confirmed that the model was a good fit, and the study's hypotheses were supported. The findings provide valuable theoretical insights and practical implications for creating more inclusive and supportive work environments to improve the retention of women in IT.